Quantification of murine olfactory receptor 691 and 78 quaternary structure in hek293 cells using spatial intensity distribution analysis - Voet, Danielle Nicole (2022)
G-protein coupled receptors (GPCR) encompass a large number of protein receptors within the human genome. Because GPCRs are involved in numerous pathways including serotonin signaling in the brain, the receptors are often targets for drug development. Recent studies have demonstrated the presence of novel olfactory receptors (ORs), a member of the GPCR family, in the murine kidney but little is known about the function, and structure of these receptors. Spatial Intensity Distribution Analysis (SpIDA) has been used to measure the quaternary state (organization of receptor subunits) and surface density of GPCR proteins in live and fixed cells. In SpIDA, intensity histograms are generated and mathematically fitted from the cell images to obtain the quantal brightness (QB) of the receptor. This receptor QB can be compared to the QB of control proteins that are known to be monomer, or larger oligomers, therefore determining the quaternary, or oligomeric state of the receptor. Olfactory receptors (ORs) are members of the GPCR protein family and are responsible for our sense of smell. Several research groups have recently shown that olfactory receptors are not only located in the olfactory organs of our noses, but also present in many other organ systems including the renal system. Activation of the Olfr78 receptor can lead to various responses in the body, ranging from changes in blood pressure to preventing the proliferation of cancer cells. It was determined that short chain fatty acids (SCFAs) act as a potential ligand for both receptors. While less studied, Olfr691 demonstrates similar structures and reactions to SCFAs, inferring that these two receptors demonstrate similar functions. Both of these receptors were studied with and without the presence of butyric acid using SpIDA in attempts to gain knowledge pertaining to the structure-function relationship of these proteins. By determining the structural context of these receptors, further investigation of the conformational changes construed by ligand binding can be deduced, alluding to binding affinity and specificity associated with these ORs. This enables them to be further studied as potential targets for drug therapies. Additionally, bioinformatic based approaches were employed to gain insight into the protein structure and evolutionary relationships of this receptor with other similar GPCRs.